Assessment of a primary care e-support package of automated case finding, simplified treatment algorithm and decision support to increase hepatitis B treatment uptake in primary care clinics in Australia (SIMPLY-B Study): protocol for a pilot evaluation. Issue 3 (16th March 2023) - Moussa, Dina; Wallace, Jack; Manski-Nankervis, Jo-Anne; Doyle, Joseph S; Nguyen, Long; Boyle, Douglas; Stoové, Mark A; Asselin, Jason; Valaydon, Zina; Ahad, Marvad; Glasgow, Susanne; New, Kate; et al.
Abstract : Introduction: Despite the availability of effective, subsidised hepatitis B treatment, linkage to care and treatment rates remain very low globally. In Australia, specially trained primary care physicians (general practitioner, GPs) can prescribe hepatitis B treatment, however, most hepatitis B care occurs in specialist clinics. Increasing hepatitis B management by GPs in primary care clinics is essential to achieve national hepatitis B linkage to care and treatment targets by 2030. This pilot study determines the feasibility, acceptability and effectiveness of Simply B, a novel GP hepatitis B e-support package designed to increase hepatitis B management by GPs in primary care clinics. Methods and analysis: This study will be conducted in three parts: Part A: A prospective open-label pilot intervention study, comparing the proportion of people with hepatitis B who are managed by their GP in primary care clinics before, 12 months and 24 months after implementation of the Simply B electronic hepatitis B support package. Part B: A nested qualitative health services feasibility study using semistructured interviews and thematic analysis Part C: Cost-effectiveness analysis. Ethics and dissemination: This study has received ethics approval by St Vincent's Hospital. Data management and analysis will be centralised through the Department of Gastroenterology, St Vincent's Hospital. Trial registration number: NCT05614466 .